Integration of a Support System with Feedback into a Web-Based Medical Platform: Architecture, Implementation, and Engineering Experiments - Topuzov, Edem (Computer Tools in Education, 2025)
This paper presents the architecture and implementation of a feedback support subsystem integrated into a previously developed web-oriented platform for managing medical research data. The proposed solution enables both automatic and semi-automatic error registration, as well as structured interaction between users and the support team within a closed-loop quality improvement cycle. Additionally, the paper reports the results of engineering experiments conducted to assess the system’s resilience and scalability.